Beyond Physical Access: Coping Strategies of Students with Disabilities in Navigating Higher Education – A Qualitative Case Study. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background Students with disabilities face a wide range of challenges in accessing and succeeding in higher education, beyond just physical accessibility. These include socio-emotional barriers, limited institutional support, and systemic exclusion. In resource-constrained universities, these challenges are often amplified due to infrastructural and policy limitations. This study explores the coping mechanisms employed by students with disabilities as they navigate such higher education spaces. Methods This qualitative case study was conducted at a South African public university between January 2023 and March 2025. A purposive sample of 20 students with various physical, visual, and hearing disabilities participated in the study. Data were collected through semi-structured interviews and one focus group discussion. Braun and Clarke’s thematic analysis approach was used to identify key coping strategies and barriers. Results Findings revealed that students with disabilities employed a combination of personal resilience, peer support networks, assistive technologies, and informal arrangements with lecturers to cope. Key themes included "adaptive self-reliance," "strategic social integration," and "navigating institutional silence." While some reported supportive academic staff, others experienced marginalization due to poor disability inclusion policies. Emotional exhaustion and the need for constant self-advocacy were also highlighted as significant stressors. Conclusion The study concludes that while students with disabilities demonstrate remarkable agency, their coping strategies often compensate for institutional failures rather than reflecting inclusive education. There is an urgent need for systemic reform in university disability support systems. Recommendations Higher education institutions should adopt a holistic inclusion model that goes beyond infrastructural access to include emotional, academic, and policy-level support. This includes disability training for staff, establishment of peer-mentoring programs, and investment in adaptive technologies. Institutional policies must be co-designed with students with disabilities to ensure relevance and effectiveness.